Analisis Adopsi Inovasi Pertanian Cerdas Iklim berbasis Teknologi Pertanian Presisi di Kabupaten Sleman - Nanda Ardelya; Mastur; Siti Nurlaela (Jurnal Greenation Pertanian dan Perkebunan, 2026)
The decline in chili productivity due to extreme weather anomalies in Merdikorejo Village underlies the importance of strengthening farmer capacity after the Climate Change Impact Technical Guidance through the integration of precision agriculture technology to ensure the economic sustainability of the horticultural sector. This study aims to examine the adoption process of precision agriculture technology innovations among farmers in Merdikorejo Village, Tempel Sub-district, Sleman Regency. Using a qualitative descriptive approach, this research is in the form of a case study. Data collection involved interviews with 6 (six) informants representing a combination of farmer groups, observations, and Focus Group Discussions (FGD), with triangulation techniques. The results of the study indicate that the adoption of precision agriculture technology in Merdikorejo is not simply a transfer of technical equipment, but rather a complex mental and managerial transformation through five stages of innovation diffusion. At the knowledge and persuasion stage, exposure to formal information (DPI Technical Guidance) and informal information (experiential learning) successfully triggered farmer self-efficacy to carry out off-season cultivation with a projected profit margin of 61.72%. The decision-making and implementation phases in the field triggered an agreement to accelerate the planting of the RM 21 chili variety by a core group that integrates modern technology with local wisdom (Pranata Mangsa). Furthermore, in the confirmation phase, the successful technical testing of the closed-loop system on sloping land alleviated farmers' technological anxiety. Judging by their behavioral patterns, the adoption process moved through two main pathways: a structured institutional pathway that shapes the characteristics of the early majority and a self-help pathway based on field experience that shapes the characteristics of farmer innovators. These two groups converged in a horizontal social interaction space (peer-to-peer learning) with intensive mentoring from extension workers as change agents. This synergy not only encouraged reinvention (technical modification) of components but also increased farmers' managerial capacity toward climate-smart (less-labor) agriculture. At the macro scale, the sustainability of this innovation was firmly integrated with the strengthening of auction market institutions (gathering points) that ensured commodity price stability and farmer economic sustainability.